Pengaruh Job Insecurity, Kepuasan Kerja Dan Komitmen Organisasi Terhadap Turnover Intention Karyawan Pada PT. Glow Kediri - Bambang Suwarsono; Alvia Arum Wandari; Nuraidya Fajariah (Universitas Islam Kadiri, 2022)
This study aims to determine the effect of job insecurity, job satisfaction and organizational commitment on employee turnover intention at PT.Glow Kediri. The method used in this research is descriptive quantitative. The population used in this study are employees who work at PT. Glow Kediri who are still actively working until 2022 are 74 people. The sample used in this study is daily/volume employees in the sewing department who are still working until February 2022 with a total sample of 47 people. The sampling method used in this study used purposive sampling. Data processing in this study uses validity test, reliability test, classical assumption test, multiple linear regression, t test and F test and the coefficient of determination (R2). The result of this study is that job insecurity has a partially negative effect on employee turnover intention with a significance value of 0.000 <0.05. Job satisfaction has a partial negative effect on turnover intention with a significance value of 0.004 <0.05. Organizational commitment has a partial negative effect on turnover intention with a significance value of 0.047 <0.05. job insecurity, job satisfaction and organizational commitment have a simultaneous negative effect on turnover intention with a significance value of 0.000 <0.05.